2011
DOI: 10.1136/vr.c7003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct culture versus PCR for the detection of Brucella in aborted fetuses of cattle and sheep in Turkey

Abstract: The aim of this study was to detect Brucella in samples from aborted fetuses of sheep and cattle in Turkey using PCR and bacteriological analysis, and to determine the sensitivity and specificity of the PCR. Organ homogenates from 38 aborted fetuses of cattle and 56 aborted fetuses of sheep were tested. All organ homogenates were cultured for bacteriological analysis, and all of the homogenates and the Brucella isolates obtained by culture were examined with a commercial PCR kit. On bacteriological analysis, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Therefore it is suggested that these primer pairs can also be useful for the direct detection of Brucella species in tissue samples. Also, like other studies such as those conducted by Huber et al and Kazemi et al, this study showed that PCR was a sensitive and suitable method for detecting Brucella species (25, 26). More studies will be needed to improve the specificity and sensitivity of molecular methods before recommending routine laboratory detection.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore it is suggested that these primer pairs can also be useful for the direct detection of Brucella species in tissue samples. Also, like other studies such as those conducted by Huber et al and Kazemi et al, this study showed that PCR was a sensitive and suitable method for detecting Brucella species (25, 26). More studies will be needed to improve the specificity and sensitivity of molecular methods before recommending routine laboratory detection.…”
Section: Discussionsupporting
confidence: 82%
“…Since, PCR has been developed for the detection of Brucella in a wide variety of clinical samples such as semen [24], blood [38], milk [43], aborted fetuses [8] and lymphoid tissue [17] and in all of these studies PCR has been introduced as an accurate and sensitive assay for detection of Brucella spp. To our knowledge, the volume of semen used was also a critical factor affecting the amplification reaction in our experiment.…”
Section: Statistical Analysis and Evaluation Of Ct Valuesmentioning
confidence: 99%
“…In these years many countries have accepted PCR as an accurate, fast and official assay to detection of various diseases such as BVD. Studies indicated that PCR is an accurate assay to detection of BVD's closely related disease such as Brucellosis (Buyukcangaz et al 2011), Infectious Bovine Rhinotracheitis (IBR) (Takiuchi et al 2005) and Leptospirosis (Richtzenhain et al 2002) in clinical samples like aborted fetuses.…”
Section: Discussionmentioning
confidence: 99%